From Reproductive Rights to Reproductive Justice - Marji Gold (Social Medicine Publication Group, 2019)
This month the Social Medicine Journal of-fers readers the text of the Annual Harold Wise Memorial Lecture held on June 13, 2017 at the Department of Family and Social Medicine at Montefiore Medical Center. Harold Wise was the founder of the Residency Program in Social Medicine and the award recognizes a faculty member who best represents the values of the Residency Program.